A molecular dynamics study on two promising green surfactant micelles of choline dodecyl sulfate and laurate. Issue 87 (5th September 2016) - Wei, Yaoyao; Wang, Honglei; Liu, Guokui; Wang, Zhongni; Yuan, Shiling
Abstract : Two green surfactants, made by dodecyl sulfate (DS − ) and laurate (C12) with equimolar choline (Ch + ) components as counterions, are studied through all-atom molecular dynamics simulations. Abstract : Two green surfactants, made by dodecyl sulfate (DS − ) and laurate (C12) with equimolar choline (Ch + ) components as counterions, are studied through all-atom molecular dynamics simulations. Ion-pairing between head groups and choline ions is directly analysed at the molecular level, including counter-ion binding patterns, intensity and stability. Six binding patterns exist in these two micelles. Differently, hydroxyl groups of choline in ChDS micelles have more potential to penetrate into the micelle while they are more likely to be exposed to the aqueous solution in ChC micelles. Properties of the micelle surface are also studied, giving an intuitive description of charge distribution on the micelle surface. Further, we perform a study of one pyrene (Py) molecule solubilized into the micelle to understand the relation between properties and applications.